Understanding the Oxygen Reduction Reaction Activity and Oxidative Stability of Pt Supported on Nb‐Doped TiO2. Issue 15 (1st August 2019) - He, Cheng; Sankarasubramanian, Shrihari; Matanovic, Ivana; Atanassov, Plamen; Ramani, Vijay
Abstract: Invited for this month′s cover are the groups of Prof. Vijay Ramani at Washington University in St. Louis and Prof. Plamen Atanassov at the University of New Mexico (presently the University of California, Irvine). The image represents a fuel cell‐powered car with a highly durable and active catalyst. The Full Paper itself is available at 10.1002/cssc.201900499 . Abstract : "Pt/NTO is shown to exhibit significantly greater activity than the benchmark Pt/C catalysts…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201900499 . View the Front Cover here: 10.1002/cssc.201902005 .